THE VERBAL NOMINA AGENTIS OF THE OLD RUS LANGUAGE: COGNITIVE-ONOMASSIOLOGICAL ASPECT - Ярмоленко, Галина (Linguistic Bulletin (Movoznavchyi Visnyk), 2020)
One of the urgent linguistic problems is the study of the motivation of derivative units, in particular, the verbal agent nouns of the Old Rus language. In the linguistics, motivation has traditionally been analyzed at the boundary of word formation and linguistic semantics, and has been seen as a link between two linguistic characters – the generative and the derivative. The typology of motivation was based on different principles. The development of national cognitive onomasiology has made it possible to interpret this concept in a new way and to distinguish the following types of motivation: propositional, modal, mixed, conceptual and integrative. Purpose. The purpose of the article is to investigate the verbal agentic nouns of the Old Rus language in the cognitive-onomasiological aspect: to interpret their onomasiological structure, to determine the type of motivation of these derivatives. Results. Verbal nomina agentis are usually formed as a result of predicative argumentative motivation, based on the choice of the motivator from the zone of true information about an object obtained in the course of cognitive and practical activity of nominees and represented by signs of direct importance. The semantic typology of predicates is taken into account in the analysis of verbal agent nouns. This made it possible to identify groups of names that are motivated by verbs denoting work, thinking, speech and other activities. The onomasiological structure of the nomina agentis studied necessarily contains an onomasiological trait, the onomasiological basis – a word-forming formant, optional implicit, connotative components. The semantic properties of the Old Rus language are also illustrated by redundancy. Originality. It is the first time in domestic linguistics, that cognitive-onomasiological analysis was applied to study the motivation of derivative nouns of the Old Rus language. Conclusion. The study of the verbal nomina agentis of the Old Rus language in the cognitive-onomasiological aspect shows that these derivatives are formed as a result of predicate-argumentative motivation. Their derivatives are verbs of different semantic classes. The most numerous are the group of agency names, motivated by recruiters with the value of work activity. The onomassiological structure of a number of human names contains an implicit component, a connotative characteristic